Analysis Value-Added of Red Ginger in Sarabba Syrup Product at Balla Ratea Home Industry Gowa Regency - Andi Faizal Mubarak; Nadir Nadir; Muh. Ikmal Saleh; Dewi Sartika; Sitti Arwati (Program Studi Agribisnis Universitas Muhammadiyah Sinjai, 2025)
This study aims to know the production process and analyze value-added red gingger on sarabba syrup products in Balla Ratea Home Industry, Taeng Village, Palangga District, Gowa Regency. The method of determining informants in this study was purposive sampling with the provision that the owner of the SMEs (Small and Medium Enterprises) Balla Ratea Home Industry in Gowa Regency along with its treasurer and members were the main informants in this study. This study used the Hayami method data analysis technique to determine the added value of red ginger in sarabba syrup products. Research results showed that the process of producing ginger into sarabba syrup product in Balla Ratea Home Industry starting from the washing and peeling process, boiling and extraction, filtering, mixing and cooking, sterilization, cooling, packaging and storage. The amount of value-added in the sarabba syrup product in Balla Ratea Home Industry is Rp. 378,400/kg and the value-added ratio is 77.99%. The value-added of processed ginger products is in the high category.